A Study for More Important Aerobic Diarrheal Bacteria in Children of AI-Qadisiya Governorate and its Susceptibility to Some Antibiotics: Jmela R. Esmaeel , Hassan A. Abdul-Ratha , And Adnan H. Abeed - Esmaeel, Jmela R. (The Iraqi Journal of Veterinary Medicine, 2009)
This study was conducted to investigate the dominate aerobic bacterial agents causing diarrhea in childrenand study its susceptibility against some antibiotics.For this goal, 460 stool specimens were collected from infected children aged from 1 month to 5 years atDiwaniya teaching hospital for obstetrics and pediatrics from April up to November 2004, study includealso the evaluation of some factors (age, sex, and residence area) on infected with diarrhea.Samples were cultured on different selective and differential media include blood agar, MacConkey agarand S-S agar and identified them by using biochemical tests with ensuring the results by API-20E systemand serological tests ..Results showed the obtaining of 214 bacterial isolates belonging to seven different genera (E.coli,Salmonella, Proteus, Klebsiella, Shigella, Enterobacter and Staphylococcus aureus) with the percentage(45.79%, 14.94%,13.08%, 12.61 %,10.7%,1.86%, and 0.93%) respectively.The study showed that there are no differences between increases or decrease of diarrhea infection andseason or month and the highest ratio of infection were in September, August, June, and May.Regarding age influences, the first age class (1-6) months was subjected to infection more regarding sex. Itappeared that the percentage of infection in male was 60.43% in compare with females 39.5% while theratio of infection in city’s children was 68.47%, whereas in village’s children it was 31.52%.Susceptibility test of these isolates to different antibiotics by using disc diffusion method showed that mostof these bacterial isolates were sensitive (100%) to ciprofloxacin and resistant (100%) to Ampicillin, whilediffered in its sensitivity to the other antibiotics.